Crafts and social networks in Viking towns - Ashby, Steven P.; Sindbæk, Søren M. (Oxbow Books, 2020)
Crafting Communities explores the interface between craft, communication networks, and urbanization in Viking-age Northern Europe. Viking-period towns were the hubs of cross-cultural communication of their age, and innovations in specialized crafts provide archaeologists with some of the best evidence for studying this communication. The integrated results presented in these papers have been made possible through the sustained collaboration of a group of experts with complementary insights into individual crafts. Results emerge from recent scholarly advances in the study of artifacts and production: first, the application of new analytical techniques in artifact studies (e.g. metallographic, isotopic, and biomolecular techniques) and second, the shifted in interpretative focus of medieval artifact studies from a concern with object function to considerations of processes of production, and of the social agency of technology. Furthermore, the introduction of social network theory and actor-network theory has redirected attention toward the process of communication, and highlighted the significance of material culture in the learning and transmission of cultural knowledge, including technology. The volume brings together leading UK and Scandinavian archaeological specialists to explore crafted products and workshop-assemblages from these towns, in order to clarify how such long-range communication worked in pre-modern Northern Europe. Contributors assess the implications for our understanding of early towns and the long-term societal change catalysed by them, including the initial steps towards commercial economies. Results are analyzed in relation to social network theory, social and economic history, and models of communication, setting an agenda for further research. Crafting Communities provides a landmark statement on our knowledge of Viking-Age craft and communication